Single Atrium- A Case Report (KYAMC Journal, 2019)
Single atrium is a rare congenital heart disease in which there is developmental absence of both septum primum and secondum part of atrial septum. this report of rare case is to share our experience in surgery for Single atrium. Patient with single atrium with persistant left superior venacava (PLSVC) and left sided Inferior venacava (IVC) underwent gluteryldehye treated autologous pericardial patch closure, separating the two atria and leaving the coronary sinus, both PLSVC and Left IVC in the right atrial side and drainage of all four pulmonary vein into Left atrium. Post operatively there was no conduction defects in electrocardiogram and echocardiogram showed no residual shunt across the neoatrial septum. The long-term survival of surgical correction of single atrium is good. To avoid injury to the conduction system one has to be utmost careful by keeping the sutures remote and superficial from the bundle.KYAMC Journal Vol. 10, No.-1, April 2019, Page 54-56